Enhancing public dialogue about inclusion in school education: a citizens’ panel pilot - Norwich, Brahm; Webster, Rob (Frontiers in Education, 2024)
Introduction: This paper reports on a small-scale Citizens’ Panel pilot project using deliberative democratic methods to produce policy ideas about inclusion in school education of young people with special educational needs and disabilities (SEN/D) in England. The project had two aims: i) to obtain information about modifying a Citizens’ Panel process to enhance the effective participation of young people with SEN/D; and ii) to generate more nuanced, grounded and integrated policy ideas about inclusion than can be found in recent English school education policy. Methods: The Citizens’ Panel was a two phase deliberative process. Phase 1 involved working with six young people with SEN/D and their parents/carers to shape the Citizens’ Panel agenda, and to obtain information about how they could participate and communicate their perspectives during the events. Phase 2 involved the delivery of the Citizens’ Panel itself, which comprised 28 people: the six young people from phase 1, plus four young people without SEN/D, 13 parents/carers, and five education professionals. Results: The process evaluation revealed the need for and impact of meticulous planning using a differentiated and strengths-based approach to design. While participants reported that taking part in the Citizens’ Panel was overall, a positive and worthwhile experience, the differentiated approach involved trade-offs that affected the experiences of some participants without SEN/D, though not detrimentally. The panel produced distinctive ideas about more inclusive schools, where almost all of the themes were about general school changes for everyone. Most general themes involved some specific SEN/D aspects, with only one theme being SEN/D specific. This paper illustrates how these ideas are more nuanced, grounded and integrated than those in current national policy. Discussion: This paper provides evidence of how deliberative approaches can be used within and between schools, groups of schools (e.g. multi academy trusts), local networks (including local authorities), as well as at the national level. Lessons drawn show how deliberative methods used by advocacy groups, protest movements and non-governmental organisations in support of more transformational change can be developed in ways that enable young people with SEN/D to participate and have their voices heard.